ENGLISH TEACHERS' CULTURAL BACKGROUND AND THEIR TEACHING BELIEF - Wulandari, Heidy (Lire Journal (Journal of Linguistics and Literature), 2019)
This paper is a non-research article which aims at elaborating the relation between teachers’ cultural background and their teaching beliefs. Way of thinking, behaviour, value, tradition, and belief in a society are taken into account as aspects of cultural background in this paper. Meanwhile belief is considered as unchangeable principle set in teachers’ personality which has impact on what they do in the classroom. The red line between cultural background and teachers’ beliefs has positive and negative side. Thus it is important for teachers to rely not only on their belief but also students’ needs and other supporting teaching aspects in order to reach a successful teaching and learning process.